Pemanfaatan Stop Motion pada Desain Iklan UNHAR - Khairunnisa, Khairunnisa; Khairani, Mufida (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
The stopmotion method is an animation method that takes several images and converts the images into video form, creating an illusion so that the images appear to be moving. This method is used to make the University of Harapan Medan advertisement look attractive and unique so that it is accessible to all groups. It is hoped that this can help as a form of promotion and marketing from University of Harapan Medan